Qualitative and Quantitative Molecular Analysis of Epstein-Barr Virus in Iraqi Patients with Relapsing-Remitting Multiple Sclerosis - Ad'hiah, Ali H.; Atiyah, Noor S.; Fadhil, Hula Y. (Iraqi Journal of Science, 2023)
Multiple sclerosis (MS) is a neuro-inflammatory disorder in which the Epstein-Barr virus (EBV) is proposed to have a pathogenic role. Therefore, a case-control study was performed (93 patients with relapsing-remitting MS and 113 healthy controls (HC) to analyze the prevalence and viral load of EBV infection using real time-polymerase chain reaction. Prevalence of EBV infection was lower in patients compared to HC but the difference was not significant (12.9 vs. 21.2%; probability [p] = 0.187). EBV-positive MS cases were more common in females than in males (83.3 vs. 16.7%), while an opposite distribution was observed in HC (37.5 vs. 62.5%), and the difference was significant (p = 0.041). Blood group O frequency was higher in EBV-positive patients compared to the corresponding HC but the difference was not significant (33.3 vs. 20.8%; p = 0.443). EBV-positive MS cases showed similar frequency in the two groups of the expanded disability status scale (EDSS: < 3.0 and ≥ 3.0; 50% each). EBV load was significantly elevated in EBV-positive MS cases compared to EBV-positive HC (94.6 ± 84.2 vs. 17.0 ± 16.3 DNA copy/100 cells; p = 0.009). When EBV-positive MS cases were classified by gender, EDSS groups or ABO blood groups, there were no significant differences between EBV loads in each stratum. However, a significant correlation between EBV load and EDSS was found (correlation coefficient = 0.620; p = 0.031). In conclusion, the prevalence of EBV infection showed no significant differences between MS patients and HC, while EBV load was significantly higher in patients.